Improved Methodology for the Synthesis of a Cathepsin B Cleavable Dipeptide Linker, Widely Used in Antibody-Drug Conjugate Research. Issue 40 (3rd October 2018) - Mondal, Deboprosad; Ford, Jacob; Pinney, Kevin G.
Graphical abstract: Highlights: A revised synthesis was developed for the Val-Cit linker widely employed in ADCs. The methodology proved to be high-yielding, reproducible, and devoid of epimerization. A new drug-linker construct bearing a novel tubulin-active payload was synthesized. Abstract: Antibody-drug conjugates (ADCs) represent an emerging class of biopharmaceutical agents that deliver highly potent anticancer agents (payloads) selectively to tumors or components associated with the tumor microenvironment. The linker, responsible for the connection between the antibody and payload, is a crucial component of ADCs. In certain examples the linker is composed of a cleavable short peptide which imparts an additional aspect of selectivity. Especially prevalent is the cathepsin B cleavable Mc-Val-Cit-PABOH linker utilized in many pre-clinical ADC candidates, as well as the FDA approved ADC ADCETRIS ® (brentuximab vedotin). An alternative route for the synthesis of the cathepsin B cleavable Mc-Val-Cit-PABOH linker is reported herein that involved six steps from l- Citrulline and proceeded with a 50% overall yield. In this modified route, the spacer (a para -aminobenzyl alcohol moiety) was incorporated via HATU coupling followed by dipeptide formation. Importantly, this route avoided undesirable epimerization and proceeded with improved overall yield. Utilizing this methodology, a drug-linker construct incorporating a potent small-molecule inhibitor of tubulin polymerization (referred to as KGP05), was synthesized as a representative example.